Improved detection of intracerebral hemorrhage with transcranial ultrasound perfusion imaging - Kern, Rolf; Kablau, Micha; Sallustio, Fabrizio; Fatar, Marc; Stroick, Mark Gregor; Hennerici, Michael G.; Meairs, Stephen (Cerebrovascular diseases, 2008)
Background: Ultrasound perfusion imaging (UPI) is a new approach for the assessment of brain perfusion. In contrast to the increasing experience with this method in patients with ischemic stroke, data on the value of UPI for the diagnosis of intracerebral hemorrhage (ICH) are lacking. Methods: We investigated 12 consecutive patients with sufficient temporal bone windows and a CT diagnosis of acute supratentorial ICH (basal ganglia n = 9 and lobar n = 3). Native transcranial B-mode ultrasound and UPI studies with echo contrast agents were performed on day 1 and on days 5-7 including volume measurements using the maximum extension on transverse and coronal ultrasound planes. Results: ICH was identified as hyperechogenic mass on B-mode ultrasound in 11/12 patients, but the correlation with CT volume measurements was poor (day 1: r = 0.4, 95% confidence interval, CI: -0.23-0.79; p = 0.1; follow-up: r = 0.58, 95% CI: 0.04-0.86; p = 0.21). Volume measurement was more precise using UPI with a significant correlation on day 1 (r = 0.8, 95% CI: 0.47-0.94; p < 0.001) and during the follow-up (r = 0.94, 95% CI: 0.81-0.98; p < 0.001). Using UPI the typical finding was a focal reduction of contrast agent arrival in the ICH core which led to better delineation of the lesion borders from adjacent tissue. Depiction of lobar ICH was difficult with ultrasound, and lesion sizes tended to be underestimated. Conclusions: This study supports earlier work demonstrating the usefulness of native transcranial ultrasound for the diagnosis of ICH. UPI further improves diagnostic reliability and allows very precise ICH volume measurements. If confirmed in larger studies, this approach may be useful for bedside monitoring of ICH progression and regression.
Gesehen am 24.03.2021